Analysis of single nucleotide polymorphism of p16 gene in cytological samples of patients with oral potentially malignant disorders (OPMD) and oral squamous cell carcinoma (OSCC) - Neetu Oommen; Vasanthi V; Ramya Ramadoss; Rajkumar Krishnan (Oral Oncology Reports)
Background: pl6 (CDKN2a) play a role in tumorigenesis in some head and neck squamous cell carcinomas. Frequent homozygous deletions of the pl6 gene have been reported in many tumor cell lines including the brain, breast, osteosarcomas, melanomas, kidney, bladder, and ovary. Materials and methods: 5 patients without any tobacco using habit were included in group I as controls. 10 clinically and histopathologically confirmed cases of oral potentially malignant disorders (OPMDs) [oral submucous fibrosis (OSMF) −7 & leukoplakia (moderate dysplasia) −3] were included in group II. 10 clinically and histopathologically confirmed cases of OSCC were categorized as group III. Buccal scrapings were taken and analyzed for exon 1, 2, 3 of p16 and homozygous deletion in exon 2 of p16 was also detected by PCR and gel electrophoresis. Results: PCR amplification products of exon 1, 2, 3 of p16 were found in all 25 samples which include 10 cases of OSCC, 10 cases of OPMDs and 5 controls. Homozygous deletion in exon 2 was found only in 30 % of OSCC and 20 % of OPMD. Conclusion: Our study showed that cytological samples yield sufficient amount of DNA, which showed 100 % positivity with exon 1, 2, 3 of p16 gene, but the percentage of genetic alteration of p16 gene seems to be less when compared with other related studies.